Existing evidence for the layout and history of the fort (Scottish Historical and Archaeological Internet Reports, 2006)
This section considers provides details of site location and a summary of previous work. Set in the context of the fort layout, the area excavated in 2001 lies outside the porta principalis dexter, just beyond the outer defensive ditch. In this location evidence for the road and extramural settlement activity is to be expected.